Collaborate computing : networking, applications and worksharing : 12th International Conference, CollaborateCom 2016, Beijing, China, November 10-11, 2016, Proceedings /: networking, applications and worksharing : 12th International Conference, CollaborateCom 2016, Beijing, China, November 10-11, 2016, Proceedings. (2017) - Unknown
No abstract available